Aspergillus tubingensis and Talaromyces islandicus Solubilize Rock Phosphate Under Saline and Fungicide Stress and Improve Zea mays Growth and Phosphorus Nutrition (2020)
The purpose of this study was to evaluate the capability of Aspergillus tubingensis and Talaromyces islandicus to solubilize inorganic phosphorus sources, their activity under abiotic stress, and the enhancement of P availability in soils and plant growth. The P-solubilizing capability and acidification mechanism of the strains were assessed in vitro using tricalcium phosphate and rock phosphate. Independent assays were conducted with rock phosphate under NaCl and fungicides carbendazim, chlorothalonil, and propamocarb hydrochloride using a factorial design. Thereafter, the effects of fungal inoculations in rock phosphate–amended soil and P nutrition of Zea mays were assessed in a greenhouse experiment. Both fungi solubilized P in vitro via acidification through the exudation of acetic, citric, lactic, malic, quinic, and succinic acids. The P-solubilizing efficiency of A. tubingensis was maintained above 97.5% under 0.5 to 3.0% NaCl, up to 28.7% in the treatment with carbendazim, up to 5.3% with chlorothalonil, and above 96.5% with propamocarb hydrochloride; while T. islandicus efficiency decreased to 45.2% in a NaCl concentration-dependent trend, and maintained it above 80% in the fungicide treatments. The inoculation with A. tubingensis increased the available P in the amended soil by up to 65% after 30 days and resulted in 87% higher foliar P content, 111% greater plant height, and 25% greater dry weight of maize shoots. Similarly, T. islandicus contributed to these parameters in 55, 67, 90, and 17%, respectively. These findings suggest their potential as qualified phosphorus solubilizing microorganisms to develop novel and sustainable approaches for P fertilization in agriculture. © 2020, Sociedad Chilena de la Ciencia del Suelo.